Co-pyrolysis of sewage sludge and hydrochar with coals: Pyrolytic behaviors and kinetics analysis using TG-FTIR and a discrete distributed activation energy model. (1st January 2020) - He, Chao; Tang, Chunyan; Liu, Wen; Dai, Leilei; Qiu, Rongliang
Graphical abstract: Highlights: N was more likely to be stabilized in co-pyrolysis of HC with lower-rank coals. Coal/HC blends presented higher abundance of activation energy around 180 kJ/mol. High-rank coal showed remarkable synergistic effect on light hydrocarbons yield. Elevated high-rank Coal 1/HC blending ratio favored CH4 release. Co-pyrolysis of coals with HC is more sustainable for energy conversion. Abstract: Dewatered sewage sludge (DS) has been upgraded to hydrochar (HC) using hydrothermal conversion because of superior fuel quality and avoidance of energy-intensive dewatering. In order to further develop sustainable energy conversion of HC, co-pyrolysis of DS and HC with three different-rank coals have been comprehensively investigated using thermogravimetric analysis coupled with Fourier transform infrared spectrometer and a discrete distributed activation energy model. Pyrolytic behaviors, kinetics and gas releasing characteristics have been examined. Results suggest that low-rank Coal 2 and moderate-rank Coal 3 blended with DS exhibited the highest synergistic removal of N and S, respectively. Co-pyrolysis of DS with high-rank Coal 1 favored C retention and N or S removal, while N was more likely to be stabilized in co-pyrolysis of HC with lower-rank coals. A less intensive but lasting devolatilization process in higher temperature regime (362–487 °C) was expected for HC. Higher fixed carbon content in HC and coals led to higher abundance of activation energy centralized around 180 kJ/mol for coal/HC blends. At the maximum decomposition rate temperature of 293.5 °C, pyrolysis of HC generated remarkable CH4 and other combustible gases with significantly reduced CO2 . High-rank Coal 1 showed the most remarkable synergistic effect on the yield of light hydrocarbons and elevated Coal 1/HC blending ratio favored CO2 and CH4 release. Overall, co-pyrolysis of coals with HC could be a more sustainable technique for sewage sludge management and utilization in terms of stable devolatilization and centralized activation energy, higher yield of combustible syngas, and obviously reduced emissions of CO2 and nitrogen-containing gases.